The Role of Forensic Accounting in Combating Financial Crimes Resulting From Accounting Estimates - Saddam Catea Hashim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Forensic accounting plays a vital role in combating financial crimes resulting from accounting estimates, as it combines specialized knowledge in accounting with forensic investigative skills to analyze financial statements and uncover manipulations.and The research aims to explore how forensic accounting affects the identification of financial crimes related to accounting estimatesThe most important conclusions of the research were : Forensic accounting plays a vital role in discovering financial manipulations and frauds associated with accounting estimates. Through careful examination and forensic analysis of financial statements, forensic accountants are able to detect any manipulation of numbers or exaggeration of profits or losses. andThe most important recommendations include examining the necessity of implementing strict internal control procedures that include reviewing accounting estimates regularly, using forensic accounting methods. This would reduce the chances of financial manipulation and fraud, and this research contributes to clarifyingThe role of forensic accounting in detecting financial crimes related to estimatesAccounting.And improvement transparencyAnd the accuracy of financial reports by examining estimatesAccounting.andDevelop effective financial investigation strategies to combat illegal financial activities.